Impactos ambientales de la actividad metalmecánica en la construcción del cerco perimétrico de la refinería de Iquitos. 2023 - Soria Diaz, David (2024)
The study was carried out in the area of the Iquitos refinery, Amazon River, with the purpose of evaluating and analyzing the environmental impacts of the metal mechanical activity of the construction of a perimeter fence in an oil refinery. The research design is descriptive, observational and transversal in relation to the activities identified in the execution of the work. The evaluations were made through on-site inspection or direct observation of the activities to determine the environmental impacts for a period of 20 days from a perceptive and descriptive orientation, for this the modified CONESA matrix was used, adapted to the activities of the project and environmental components of the area of influence and includes the typologies of intensity, extension, moment, persistence, reversibility, periodicity, accumulation, synergy and recoverability, according to the activities and attributes and assessment scales. Which made it possible to determine that the levels of environmental impacts produced by the activities within the components and attributes evaluated, their levels of importance are low to moderate, none of the impacts have a high level of importance, so we can conclude that the The metal-mechanical activity of the EDA Manufacturing and Construction company does not cause a significant increase in soil, air and water pollution in the area where the work is being carried out, which is why the general hypothesis of the study is rejected.